A novel method to greatly increase methane hydrate exploitation efficiency via forming impermeable overlying CO2 cap. (February 2019) - Li, Nan; Sun, Zhenfeng; Jia, Shuai; Sun, Changyu; Liu, Bei; Yang, Lanying; Chen, Guangjin
Abstract: Aiming at increasing the exploitation efficiency of natural gas hydrate via decreasing the yield of water, a new idea " reservoir reformation " is proposed in this work, i.e., reforming natural gas hydrate reservoir by constructing an artificial impermeable overlying CO2 hydrate cap. Fine feasibility of this idea has been proved in this laboratory scale work. After reformation by CO2 injection to the permeable overburden, a confined environment with an impermeable CO2 hydrate cap is constructed successfully for depressurization operation. The cap can maintain mechanical stability for enough long time until the finish of production process. With the protection of the artificial CO2 hydrate cap, the production efficiency is greatly improved and the water yield is decreased remarkably. This work is of energy and environment double significance although lots of deeper and wider work should be done in future.